Preoperative Chemoradiation Therapy Decreases the Number of Lymph Nodes Resected During Esophagectomy - ÇELİKEL, ÇİĞDEM; BATIREL, HASAN FEVZİ; ERMERAK, NEZİH ONUR (SPRINGER, 2015)
Background This study aimed to analyze the effect of preoperative chemoradiation on the adequacy of lymph node dissection. Methods Patients with esophageal cancer treated with esophagectomy by the same surgeon between 2004 and 2011 were reviewed. Specimens were examined by the same pathologist. Patients were grouped into two depending on the type of treatment received. Results Forty-seven patients with curative esophagectomy were included in the study. Twenty patients had preoperative chemoradiation followed by surgery and 27 had surgery alone. Open and hybrid esophagectomy approaches were used. The average number of lymph nodes dissected was 16 +/- 10 (1-39). There was a significant decrease in the number of lymph nodes examined in patients with preoperative chemoradiotherapy in comparison to surgery alone (p = 0.001). Median length of stay was 12 days. R0 resection rate was 96 %. The median survival was 36.3 months, with a 42 % 5-year survival. Seven patients (25 %) had complete pathologic response following chemoradiation. No significant difference was recorded in terms of disease recurrence (p = 0.3). While morbidity was higher in the preoperative therapy group with 30 day mortality of 10 %, type of surgical approach does not seem to influence the number of lymph nodes dissected (p = 0.7). Conclusions Preoperative chemoradiation decreases the number of harvested lymph nodes following esophagectomy regardless of the surgical technique used. The optimum number of lymph nodes currently recommended to be dissected for accurate nodal staging and survival needs revision in this group of patients.
Keywords: RECTAL-CANCER; THORACIC ESOPHAGUS; LYMPHADENECTOMY; SURVIVAL; SURGERY; GUIDELINES; DISSECTION; CARCINOMAS; SPECIMEN